PROJECT-ACTIVITY-COOPERATIVE LEARNING-EXERCISE MODEL IN IMPROVING STUDENTS' CREATIVE THINKING ABILITY IN MATHEMATICS - M. Afrilianto; Tina Rosyana; Linda Linda; Tommy Tanu Wijaya (Jurnal Infinity, 2022)
Mathematical creative thinking ability is essential to be mastered by students to create good learning results and achievement. To install creative thinking in students' minds, they are highly requested to apply an innovative learning model. Among innovative learning models, project-activity-cooperative learning-exercise (PACE) is the one to be considered suitable for improving the students' mathematical creative thinking. This study is an experimental research using a pretest-posttest control group design. It was conducted in three classes of IKIP Siliwangi students by applying different learning models. The first class was given the PACE model treatment with Geogebra, the second class was given the PACE model treatment, and the third class was given direct learning. The instrument used tests. Based on the data analysis, we can conclude that there are differences in improving creative thinking abilities among the students who get the PACE model learning with Geogebra (PACE-G), the PACE model, and direct learning (DL). The improvement of creative students who get PACE and PACE-G models is better than those who get DL. The progress of students' mathematical creative thinking abilities obtained from PACE and PACE-G models is a high category. In contrast, improving students' creative thinking abilities who acquire DL is categorized as a medium.